Political foundations of the lender of last resort: A global historical narrative - Calomiris, Charles W.; Flandreau, Marc; Laeven, Luc (Journal of Financial Intermediation, 2016)
This paper offers a historical perspective on the evolution of central banks as lenders of last resort (LOLR). Countries differ in the statutory powers of the LOLR, which is the outcome of a political bargain. Collateralized LOLR lending as envisioned by Bagehot (1873) requires five key legal and institutional preconditions, all of which required political agreement. LOLR mechanisms evolved to include more than collateralized lending. LOLRs established prior to World War II, with few exceptions, followed policies that can be broadly characterized as implementing “Bagehot's Principles”: seeking to preserve systemic financial stability rather than preventing the failure of particular banks, and limiting the amount of risk absorbed by the LOLR as much as possible when providing financial assistance. After World War II, and especially after the 1970s, generous deposit insurance and ad hoc bank bailouts became the norm. The focus of bank safety net policy changed from targeting systemic stability to preventing depositor loss and the failure of banks. Statutory powers of central banks do not change much over time, or correlate with country characteristics, instead reflecting idiosyncratic political histories.